Analysis of the Implementation of Differentiated Learning in the Independent Curriculum at SMAN 1 Kutacane - Nurjannah Pakpahan; Khairuddin Nst; Chairunnisak; Debby Latifah Simatupang; Ovielia Putri Rahman (Sean Institute, 2026)
This study aims to determine the increase in learning outcomes after applying differentiated learning in the implementation of the Merdeka curriculum atat SMAN 1 Kutacane. Differentiated Learning is a form of effort in a series of learning that pays attention to the needs of students in terms of learning readiness, student learning profiles, interests and talents. Differentiated learning is in line with the philosophy of educational thought according to Ki Hajar Dewantara, that education provides guidance for all the natural strengths that children have. This research was conducted in Class X-1 plus A at SMAN 1 Kutacane for the 2026-2027 academic year. The research subjects were 33 students. The method used in this research is a class action research method which consists of two cycle actions, namely cycle I and cycle II. This study used a quantitative research method in the form of a written test and a qualitative research method using observation sheets and self-reflection sheets. The results showed that differentiated learning can improve learning outcomes in ICT subjects with the achievement of mastery learning, namely 72.73% in the first cycle and 90.91% in the second cycle.